2008
DOI: 10.4103/0019-5154.43219
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of tinea gladiatorum in wrestlers in Tehran (Iran)

Abstract: Background:In recent years, skin diseases in wrestling have finally received the attention they deserve. Outbreaks of tinea corporis are often associated with sports involving extensive bodily contact; such sports include wrestling. Tinea corporis gladiatorum is primarily caused by Trichophyton tonsurans, infecting wrestlers at alarming rates. The management of skin infections in wrestlers and other athletes in sports involving skin-to-skin contact entails numerous challenges, from making an accurate diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…Of these, 19 were solitary reports of an outbreak in a single sport [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] ; 3 (including 2 from Juntendo University 24,25 ) addressed a tinea epidemic due to Tricophyton tonsurans among combat-sport (mainly judo, although one also included wrestlers 26 ) competitors in Japan [24][25][26] ; 1 reported on a single measles virus outbreak involving competitors in 2 sports;hairsp 27 ; and 1 discussed the importance of sentinel surveillance sites in high school athletic departments to monitor outbreaks of CA-MRSA across a variety of sports. 28 When we excluded this latter study from analysis (because its main focus was not a specific outbreak) and counted the 3 articles on the tinea outbreak among combatsport competitors in Japan as a single outbreak, a total of 21 outbreaks or clusters were reported in the time period.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 19 were solitary reports of an outbreak in a single sport [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] ; 3 (including 2 from Juntendo University 24,25 ) addressed a tinea epidemic due to Tricophyton tonsurans among combat-sport (mainly judo, although one also included wrestlers 26 ) competitors in Japan [24][25][26] ; 1 reported on a single measles virus outbreak involving competitors in 2 sports;hairsp 27 ; and 1 discussed the importance of sentinel surveillance sites in high school athletic departments to monitor outbreaks of CA-MRSA across a variety of sports. 28 When we excluded this latter study from analysis (because its main focus was not a specific outbreak) and counted the 3 articles on the tinea outbreak among combatsport competitors in Japan as a single outbreak, a total of 21 outbreaks or clusters were reported in the time period.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, trichophyton tonsurans was the second most common fungus that was isolated from wrestlers. Although a previous study in Iran had shown low prevalence of trichophyton tonsurans in Iranian wrestlers [20] . As trichophyton tonsurans is an anthropophilic dermatophyte [34] , higher prevalence of trichophyton tonsurans in the wrestlers in our study like many other previous studies may be explained by evidence of asymptomatic fungal infection in other wrestlers [13, 31] and contamination of wrestling mats or other wrestling equipment.…”
Section: Discussionmentioning
confidence: 99%
“…22 The causative agent is always T. tonsurans. During the 1998-1999, Kohl et al found that 84% of wrestling teams had at least one case of tinea corporis gladiatorum in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…41 Swimmers, runners, soccer, water polo, and basketball players experience tinea pedis in epidemic proportions. 2,14,16,22 The current worldwide spread of this disease, through international sports competitions, sustains a need for worldwide prevention measures that should be based upon an exact knowledge, most of all distinguishing it from the usual forms of tinea corporis. We isolated onychomycosis in nine athletes (1.5%).…”
Section: Discussionmentioning
confidence: 99%